Efisiensi Efisiensi Kinerja Pekerja Penggunaan Galah Bahan Karbon dan Aluminium - Fajar Dwi Setiawan; Gani Supriyanto; Nuraeni Dwi Dharmawati (Program Studi Teknik Pertanian, Fakultas Pertanian, Universitas Jenderal Soedirman, 2025)
Harvesting is the activity of picking fresh fruit bunches from trees, collecting loose fruits, as well as gathering and transporting the fruits to a collection point (TPH) to be taken to the palm oil mill (PKS). The tools used in this harvesting process are poles made of carbon and aluminum. Carbon composite is a material that uses carbon fibers, which are strong and lightweight, though expensive. Aluminum is a metal with low strength and soft properties. This research uses a descriptive method with primary data collection directly from the field. The results show that the use of carbon and aluminum poles varies based on age (young <35 years, old >35 years). For young harvesters using carbon poles, the average workload is 20.84%, productivity is 37.25 bunches/hour, and efficiency is 95.60%. For young harvesters using aluminum poles, the average workload is 22.75%, productivity is 30.56 bunches/hour, and efficiency is 94.40%. For older harvesters using carbon poles, the average workload is 23.67%, productivity is 35.38 bunches/hour, and efficiency is 94.32%. For older harvesters using aluminum poles, the average workload is 27.22%, productivity is 28.99 bunches/hour, and efficiency is 92.57%.